RETRACTED: Relationship Between Acute Stress Responses and Quality of Life in Chinese Health Care Workers During the COVID-19 Outbreak - Zhang, Lan; Ji, Rongjian; Ji, Yanbo; Liu, Min; Wang, Renxiu; Xu, Cuiping (Frontiers in Psychology, 2021)
This study aimed to determine the relationship between acute stress and quality of life and explore their influencing factors on health care workers. A descriptive cross-sectional study was conducted, and a sample of 525 health care workers was recruited from 15 hospitals through a convenient sampling method. Participants completed an online self-report questionnaire to assess their acute stress and quality of life. Descriptive and multiple linear regression statistics were used for this analysis. The results regarding acute stress responses varied significantly among the differences in marital status, physical activity, work status, perceived risk of contracting COVID-19, and the expected duration of the pandemic. Moreover, a younger age, lack of physical activity, being a front-line medical staff, and higher acute stress scores indicated a worse quality of life. Healthcare workers' acute stress was negatively correlated with their quality of life. Therefore, the authorities should pay special attention to health care workers' mental health and provide them with timely protection during the pandemic.